COMPUTER GRAPHICS IN ENGINEERING GRAPHICS DEPARTMENT OF MOSCOW AVIATION INSTITUTE EDUCATIONAL PROCESS - Ludmila P. Bobrik; Leonid V. Markin (Открытое образование (Москва))
Current state of technical universities students’ engineering grounding and “Engineering graphics” course place in MAI are analyzed in this paper. Also bachelor degree problems and experience of creation of issuing specialty based on «Engineering graphics» department are considered.